Properties of wood plastic composites from Petai Belalang (Leucaena leucocephala) / Larisstina Sinteh - Sinteh, Larisstina (2006)
Wood plastic composites was produced from sawdust of Petai Belalang (Leucaena leucocephala) mixed with Polypropylene (PP). To investigate the effect of 10%, 30% and 50% filler loadings on the mechanical and physical properties of wood plastic composites. The results show that the strength decreased when filler loadings increase. The flexural modulus increases at higher filler loadings while the tensile modulus was lowest at 50% filler loading. The physical properties, an increase in the filler loadings resulted in high water absorption and thickness swelling. In conclusion, Petai Belalang sawdust can be used as filler in the manufacture wood plastic composites where strength factor is not necessity.